MGNREGA : EFFECTIVENESS OF MGNREGA IN HARYANA “A CASE STUDY OF VILLAGE- RANSIKA - kumar, Dr Satish; Ms. Amrita (Innovative Research Thoughts, 2017)
Ransika is a small village located in Pataudi Tehsil of Grugaon District Haryana. In the Ransika village total 169 families lived. Total population of Ransika village has 973 people 497 are males while 476 female per population census 2011. In Ransika village population of children with age (0-6) is 148. In Ransika village out of total population (973), 54 household has applied for registration under MGNREGA and Gram Panchayat issued the job card to the household. But women participation is very low in MGNREGA activity in Ransika village.